Photograph 51 - Ziegler, Anna (Oberon modern plays., 2015)
"'The instant I saw the photograph my mouth fell open and my pulse began to race.' Does Rosalind Franklin know how precious her photography is? In the race to discover the secret of life it could be the one to hold the key. With rival scientists everywhere looking for the answer, who will be first to see it and more importantly, understand it? Anna Ziegler's extraordinary play looks at the woman who helped unlock DNA's double helix and asks what is sacrificed in the pursuit of science, love and a place in history."--Publisher's website